Sensitivity of a Model Reptile, the Common Snapping Turtle (Chelydra serpentina), to In Ovo Exposure to 2, 3, 7, 8‐Tetrachlorodibenzo‐p‐Dioxin and Other Dioxin‐Like Chemicals. (29th December 2021) - Doering, Jon A.; Brinkmann, Markus; Lucio, Maria; Stoeck, Serena; Vien, Alex; Petersen, Stephanie; Rhen, Turk; Jones, Paul D.; Hecker, Markus; Schroeder, Anthony
Abstract: Reptiles represent the least‐studied group of vertebrates with regards to ecotoxicology and no empirical toxicity data existed for dioxin‐like chemicals (DLCs). This lack of toxicity data represents a significant uncertainty in ecological risk assessments of this taxon. Therefore, the present study assessed early‐life sensitivity to select DLCs and developed relative potencies in the common snapping turtle ( Chelydra serpentina ) as a model reptile. Specifically, survival to hatch and incidence of pathologies were assessed in common snapping turtle exposed in ovo to serial concentrations of the prototypical reference congener 2, 3, 7, 8‐tetrachlorodibenzo‐ p ‐dioxin (TCDD), and three other DLCs of environmental relevance, namely, 2, 3, 4, 7, 8‐pentachlorodibenzofuran (PeCDF), 2, 3, 7, 8‐tetrachlorodibenzofuran (TCDF), and 3, 3′, 4, 4′, 5‐pentachlorobiphenyl (PCB 126). In ovo exposure to TCDD, PeCDF, TCDF, and PCB 126 caused a dose‐dependent increase in early‐life mortality, with median lethal doses (LD50s) of 14.9, 11.8, 29.6, and 185.9 pg/g‐egg, respectively. Except for abnormal vasculature development, few pathologies were observed. Based on the measured LD50, common snapping turtle is more sensitive to TCDD in ovo than other species of oviparous vertebrates investigated to date. The potencies of PeCDF, TCDF, and PCB 126 relative to TCDD were 1.3, 0.5, and 0.08, respectively. These relative potencies are within an order of magnitude of World Health Organization (WHO) TCDD‐equivalency factors (TEFs) for both mammals and birds supporting these TEFs as relevant for assessing ecological risk to reptiles. The great sensitivity to toxicities of the common snapping turtle, and potentially other species of reptiles, suggests a clear need for further investigation into the ecotoxicology of this taxon. Environ Toxicol Chem 2022;41:175–183. © 2021 SETAC